2007
DOI: 10.1007/s10194-007-0359-x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine, patent foramen ovale and migraine triggers

Abstract: Little information exists about a causal association between PFO and migraine. Some patients identify Valsalva-provoking activities (VPA) as migraine triggers. Therefore, we speculate about a pathogenic connection. The object of the study is to investigate the prevalence of right-to-left shunt (RLS) in a cohort of patients suffering migraine with aura (MA) and its possible association with migraine attacks triggered by VPA. We investigated the circumstances triggering the migraine attacks, in a consecutive ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
0
24
0
2
Order By: Relevance
“…The balloon diameter at PFO closure corresponded to the degree of RLS in this study; however, no correlation coefficient was reported [6]. In one study, migraineurs with aura were more likely to have headache triggers associated with Valsalva-provoking activities and have larger RLS than migraineurs without aura [30]. Spontaneous large RLS and MA+ were both risk factors for recurrent stroke in patients with PFO (large RLS OR 2.42, 95% CI 1.66-5.04; MA+ OR 3.87, 95% CI 1.75-8.50) [31].…”
Section: =04 P=05)mentioning
confidence: 53%
“…The balloon diameter at PFO closure corresponded to the degree of RLS in this study; however, no correlation coefficient was reported [6]. In one study, migraineurs with aura were more likely to have headache triggers associated with Valsalva-provoking activities and have larger RLS than migraineurs without aura [30]. Spontaneous large RLS and MA+ were both risk factors for recurrent stroke in patients with PFO (large RLS OR 2.42, 95% CI 1.66-5.04; MA+ OR 3.87, 95% CI 1.75-8.50) [31].…”
Section: =04 P=05)mentioning
confidence: 53%
“…There is no data in the literature showing the association between cardiovascular diseases and chronic migraine. First papers suggest the association between migraine and patent foramen ovale 27 , but this has not been confirmed in subsequent studies 28 . There are no specific papers on the association of patent foramen ovale and chronic migraine.…”
Section: Cardiovascular Diseasesmentioning
confidence: 95%
“…Control group 12/8 11.5 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) patients with RLS tend to report Valsalva-provoking activities to trigger their headache attacks [30]. We also consider the Valsalva maneuver may suggest that opening of RLS acted as a trigger for migraine attack.…”
Section: Discussionmentioning
confidence: 96%